2005
DOI: 10.1523/jneurosci.1645-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofALS2Function Is Insufficient to Trigger Motor Neuron Degeneration in Knock-Out Mice But Predisposes Neurons to Oxidative Stress

Abstract: Amyotrophic lateral sclerosis (ALS), the most common motor neuron disease, is caused by a selective loss of motor neurons in the CNS. Mutations in the ALS2 gene have been linked to one form of autosomal recessive juvenile onset ALS (ALS2). To investigate the pathogenic mechanisms of ALS2, we generated ALS2 knock-out (ALS2 Ϫ/Ϫ ) mice. Although ALS2 Ϫ/Ϫ mice lacked obvious developmental abnormalities, they exhibited age-dependent deficits in motor coordination and motor learning. Moreover, ALS2Ϫ/Ϫ mice showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 30 publications
2
99
3
3
Order By: Relevance
“…Consistent with these observations, Devon et al showed that Als2 -/-mice reveal Rab5-dependent fusion of early endosomes, and a disturbance in endosomal transport of insuline-like growth factor 1 and brain-derived neurotrophic factor receptors [19]. Surprisingly, these Als2 -/-mice did not show any obvious clinical, histopathological, or electrophysiological signs of neuronal degeneration [12,19,34]. The latter could be due to compensations during development.…”
Section: Alsinmentioning
confidence: 81%
“…Consistent with these observations, Devon et al showed that Als2 -/-mice reveal Rab5-dependent fusion of early endosomes, and a disturbance in endosomal transport of insuline-like growth factor 1 and brain-derived neurotrophic factor receptors [19]. Surprisingly, these Als2 -/-mice did not show any obvious clinical, histopathological, or electrophysiological signs of neuronal degeneration [12,19,34]. The latter could be due to compensations during development.…”
Section: Alsinmentioning
confidence: 81%
“…The generation of ALS2 −/− mice, rotarod test and histological analysis were conducted as previously described [1]. Survival data were analyzed using a log-rank test and statistical significant differences were at a minimal level of significance of p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, mutations in a second ALS-related gene (ALS2) were identified that cause a rare recessive form of juvenile onset ALS [5,9]. Previously, we and others have generated ALS2 knockout (ALS2 −/− ) mice that failed to display any obvious motor neuron degeneration [1,4]. Since over-expression of ALS2 protects cells from SOD1-mediated cytotoxicity and loss of ALS2 predisposes neurons to paraquat-induced oxidative stress [1,7], ALS2 may serve as a risk factor for motor neuron disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: an N-terminal regulator of chromatin condensation (RCC1)-like domain, which resembles the GEF for the Ran GTPase; a middle Dbl homology (DH)-and pleckstrin homology (PH)-like domain similar to the GEF for Rho GTPase; and a Cterminal vacuolar protein sorting 9 (VPS9)-like domain that is homologous to the Rab GTPase GEF (26,54). The exact mechanism by which mutations in ALS2 lead to ALS-like disease remains unknown, and this is confounded by the fact that motor neuron degeneration is not observed in ASL2 knockout mice (23). Interestingly, however, ALS2 knockout mice do have increased susceptibility to paraquat-induced neuronal oxidative stress (23), lymphopenia and hematopoiesis abnormalities (40), and endosome trafficking defects (34).…”
Section: Als2 and Sod1 Inherited Forms Of Als Exhibit Defects In Rac1mentioning
confidence: 99%